If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -8) + -7x = 1 Reorder the terms: 4(-8 + 2x) + -7x = 1 (-8 * 4 + 2x * 4) + -7x = 1 (-32 + 8x) + -7x = 1 Combine like terms: 8x + -7x = 1x -32 + 1x = 1 Solving -32 + 1x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 1x = 1 + 32 Combine like terms: -32 + 32 = 0 0 + 1x = 1 + 32 1x = 1 + 32 Combine like terms: 1 + 32 = 33 1x = 33 Divide each side by '1'. x = 33 Simplifying x = 33
| 28-4x=5x+1 | | 7+4n+6n=13 | | 9z+10=10z-21 | | 10z-21=4z+46 | | 4z+46=10z-21 | | 7z-21=10z-4 | | 10z-4=7z+21 | | 1/3y+5=8 | | 5y=34 | | 35x^2+24x-188=0 | | 35x^2-24x-188=0 | | 4x^2-4x-24= | | 2y+3=y+29 | | 2y+3=3y-33 | | (9+x)(3x+10)= | | y+29=3y-33 | | -210/48 | | 1.5(x+8)=6.4+0.8 | | 9.6x=23.04 | | 0=X^2+X+3 | | 1024=x-252 | | P(x)=x-252 | | 1/6x | | (14*(1/6))-(10(11/24)) | | 1/5+x=7/12 | | 7x+6y=5 | | x-11=69 | | 3y=-0.09 | | 3x+c=5y | | .07x+.38=-.16-.05x | | 1-5(2x-4)=12 | | 3x+5+12x+7x=-14x-12+1 |